Novel myopathy in a newborn with Shwachman–Diamond syndrome and review of neonatal presentation. Issue 5 (11th February 2016) - Topa, Alexandra; Tulinius, Mar; Oldfors, Anders; Hedberg‐Oldfors, Carola
Abstract : Shwachman–Diamond–Bodian syndrome (SDS) is a pleiotropic disorder in which the main features are bone marrow dysfunction and pancreatic insufficiency. Skeletal changes can occur, and in rare cases manifest as severe congenital thoracic dystrophy. We report a newborn boy with asphyxia, narrow thorax, and severe hypotonia initially suggesting a neuromuscular disease. The muscle biopsy showed myopathic changes with prominent variability in muscle fiber size and abnormal expression of developmental isoforms of myosin. The myofibrils showed focal loss and disorganization of myofilaments, and thickening of the Z‐discs including some abortive nemaline rods. The boy became permanently dependent on assisted ventilation. Pancreatic insufficiency was subsequently diagnosed, explaining the malabsorption and failure to thrive. Except transitory thrombocytopenia and leukopenia, no major hematological abnormalities were noted. He had bilateral nephrocalcinosis with preserved renal function. Transitory liver dysfunction with elevated transaminase levels and parenchymal changes on ultrasound were registered. The clinical diagnosis was confirmed by detection of compound heterozygous mutations in SBDS using whole‐exome sequencing: a recurrent intronic mutation causing aberrant splicing (c.258+2T>C) and a novel missense variant in a highly conserved codon (c.41A>G, p.Asn14Ser), considered to be damaging for the protein structure by in silico prediction programs. The carrier status of the parents has been confirmed. This case illustrates the challenges in differential diagnosis of pronounced neonatal hypotonia with asphyxia and highlights the muscular involvement in SDS. To our knowledge, this is the first report of myopathy evidenced in a patient with clinically and molecularly confirmed SDS. © 2016 Wiley Periodicals, Inc.